Introduction to Jesuit Pedagogy in Colonial Brazil Humanist Education and the Ratio Studiorum/ Introdução Ã Pedagogia Jesuíta no Brasil Colonial. Educação Humanista e o Ratio Studiorum (Bilingual Edition) - Lorenz, Karl (Cadernos de História da Educação, 2018)
AbstractIn 1599 the Society of Jesus approved the Ratio atque Institutio Studiorum Societatis Iesu (Method and System of the Studies of the Society of Jesus). The document outlined policies and procedures on the administration, curriculum and teaching practices in its educational institutions in Europe and abroad. Part of the Ratio detailed a secondary program of studies in classical languages and literature. The subject of this study is the program of humane letters and the focus of the analysis is the professional behavior of the Jesuit teacher responsible for its implementation. This paper identifies the actions that a Brazilian Jesuit would have taken when teaching the humanities in a Brazilian college in the 17th and 18th centuries. His pedagogical actions and activities are inferred from the "Common Rules for the Teachers of the Lower Classes" of the Ratio Studiorum.Keywords: Society of Jesus. Ratio Studiorum. Curriculum. Teaching Practices.ResumoEm 1599 a Sociedade de Jesus aprovou o Ratio atque Institutio Studiorum Societatis Iesu ("Metodo e Sistema de Estudos da Companhia de Jesus"). O documento delineou as políticas, os procedimentos administrativos, os currículos e as práticas de ensino em suas instituições educacionais na Europa e no exterior. Uma parte da Ratio detalhou um programa de estudos das línguas e da literatura clássica. O objeto deste estudo é o programa das letras humanas e o foco da análise é o comportamento profissional do professor jesuíta responsável por sua implementação. Este trabalho identifica as ações que um jesuíta brasileiro teria demonstrado quando ensinando as humanidades em um colégio brasileiro nos séculos 17 e 18. Suas ações e atividades pedagógicas são inferidas das "Regras comuns para os professores das classes mais baixas" explicitadas no Ratio Studiorum.Palavras-chave: Companhia de Jesus. Ratio Studiorum. Currículos. Práticas de Ensino.ResumenEn 1599 la CompaÃ±ía de Jesús aprobó el Ratio atque Institutio Studiorum Societatis Iesu ("Método y sistema de los estudios de la CompaÃ±ía de Jesús"). El documento describe las políticas y procedimientos sobre la administración, el plan de estudios y las prácticas de enseñanza en sus instituciones educativas en Europa y en el extranjero. Parte del Ratio detalla un programa secundario de estudios en lenguajes clásicos y literatura. El tema de este trabajo es el programa de letras humanas y el enfoque del análisis es el comportamiento profesional del profesor jesuita responsable por su implementación. Este documento identifica las acciones que un profesor jesuita habría tomado al enseñar humanidades en un colegio brasileño en los siglos 17 y 18. Sus acciones y actividades pedagógicas se deducen de las "Reglas Comunes para los Profesores de las Clases Inferiores" del Ratio Studiorum.Palabras-clave: Compañia de Jesús. Ratio Studiorum. Plan de estudios. Prácicas de enseñanza.